OXIDATION OF BENZALDEHYDE BY QUINOXALINIUM DICHROMATE - Anbarasu, K; GEETHA, N. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The kinetics and mechanism of oxidation of benzaldehyde by quinoxalinium dichromate has been studied in the presence of perchloric acid in 70 % acetic acid - water medium. The reaction follows first order with respect to benzaldehyde, quinoxalinium dichromate and fractional order with respect to perchloric acid. There is no effect on the reaction rate with increase in ionic strength of the medium by adding sodium perchlorate. The rate of reaction increases with increase in the percentage of acetic acid. The reaction does not induce the polymerization with acrylonitrile. The rate of reaction decreases with increase in the concentration of manganoussulphate. The thermodynamic and activation parameters have been calculated and a probable mechanism has been proposed.